GREEN PACKAGING AND BRANDING IMPACT ON GREEN PURCHASE INTENTION WITH GREEN BRAND IMAGE AS MEDIATOR: STUDY AT LOVE BEAUTY AND PLANET ON GEN Z IN WEST JAVA - Dewi, Cindy Fresilia; Sari, Diana (Journal of Business Studies and Management Review, 2025)
In the present era, there has been a widespread global adoption of environmental consciousness, leading to a swift transformation in people's actions and attitudes. Observing this occurrence, companies are starting to adjust and incorporate environmental considerations into account by creating and producing environmentally sustainable products or services. One of the ways of contributing is by providing sustainable packaging options for their products. This article aims to examine the influence of green packaging and branding on the intention of Generation Z consumers in West Java to purchase Love Beauty and Planet items that are environmentally friendly. A digital survey was undertaken to gather data from 255 individuals. Subsequently, the questionnaire data was analyzed using Structural Equation Modelling (SEM) employing the Partial Least Squares (PLS) technique through SmartPLS 4. In the end, this study found that Gen Z in West Java sees green packaging and branding as a significant direct force towards green purchase invention. This study also found that green brand image is an important factor in driving green purchase intention. However, this study concentrates on a particular brand and customer profile. Therefore, future research can investigate different brands or specialized markets as the primary subject.